Improvement of Research Proposal Writing Skills for PSDKU USU Lecturers in North Nias - Gea, Saharman; Rahmawaty; Iskandar Zulkarnain (Talenta Publisher, 2025)
The Tridharma of Higher Education mandates that higher education institutions conduct education, research, and community service (Article 1, Clause 9, Law No. 12 of 2012 on Higher Education). Research is a methodical endeavor that adheres to scientific principles and methodologies to collect information, facts, and explanations pertinent to the comprehension and/or examination of a field within science and technology. The USU Abdimas Team's community service is to consistently educate and support academics at PSDKU USU Nias Utara, hence addressing the research aspect of the Tridharma of Higher Education. The given materials are: (1). The resources seek to elucidate research concepts and offer guidance on building a well-structured proposal in accordance with scientific standards and research ethics. Two. The procedure for formulating a suitable proposal grounded in scientific principles and research ethics is addressed in the section. Three. Investigating local potential to be elevated as research topics, and (4). There are techniques for forging links in research initiatives. The aforementioned four materials are considered particularly advantageous for cultivating a research culture among academics at PSDKU USU Nias Utara. This commences with improving their expertise in research planning, hence facilitating the execution of the SDGs point 4 initiative, Quality Education. Quality Education is a fundamental component of the Sustainable Development Goals (SDGs). Due to the time limitations of in-person training, mentoring has transitioned online, with the anticipation that the training participants will generate many high-quality research proposal drafts.